2017
DOI: 10.1007/s00059-017-4631-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of right ventricular diastolic dysfunction on clinical outcomes in inferior STEMI

Abstract: Presence of RRVFP is associated with in-hospital mortality in patients presenting with their first IWMI complicated by RVMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…These results can be explained by a report from the SHOCK registry published in 2003, which stated that RVMI does not influence in-hospital mortality rates on patients in cardiogenic shock [13]. Moreover, recent studies have shown that in-hospital mortality after inferior myocardial infarction with RVMI depends on the presence of restrictive right ventricular filling [14]. In our study, we did not evaluate the echocardiographic findings, this remains a subject of interest for a further studies.…”
Section: In-hospital Mortalitymentioning
confidence: 70%
“…These results can be explained by a report from the SHOCK registry published in 2003, which stated that RVMI does not influence in-hospital mortality rates on patients in cardiogenic shock [13]. Moreover, recent studies have shown that in-hospital mortality after inferior myocardial infarction with RVMI depends on the presence of restrictive right ventricular filling [14]. In our study, we did not evaluate the echocardiographic findings, this remains a subject of interest for a further studies.…”
Section: In-hospital Mortalitymentioning
confidence: 70%
“…MACE developed in 5 patients of which 4 patients complicated during hospital stay. B Altıntaş also reported that all the MACE in his study developed during the hospital stay [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the usual history and physical examination, myocardial ischemia may also be associated with abnormalities in the electrocardiogram (ECG) and increased biochemical markers like cardiac troponins 4 . Inferior infarcts are to blame for poor results 5 . Reduced blood flow to the atrioventricular node (AV) due to an inferior MI can result in complete atrioventricular block (CAVB).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced blood flow to the atrioventricular node (AV) due to an inferior MI can result in complete atrioventricular block (CAVB). This condition is often short-lived, lasting for little more than two weeks 5 . Hemi-blocks may come before CAVB 6 .…”
Section: Introductionmentioning
confidence: 99%